ANALISIS KEMISKINAN MULTIDIMENSI MASYARAKAT GORONG-GORONG KELURAHAN KEBUN SIRIH DI KABUPATEN MIMIKA - Karina Sukardi (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2021)
The purpose of this research is to find out the multidimensional poverty of the people of Gorong-rong Kebun Sirih Village in Mimika Regency. Data collection techniques used to obtain data in this study are observation techniques, interviews, documentation, questionnaires. The analysis used in this study is an analysis with the Multidimensional Poverty Index (IKM).The results of this study show that the conditions experienced by the people of Gorong-rong such as lighting sources still use petromak, lamps or other, cooking fuel still uses firewood and kerosene, the roof of the house still uses zinc that is not worth using,the floor of the house still uses low quality boards and the walls of the house still use zinc and unfit boards because the community lacks access to basic infrastructure and the poverty experienced by the sewer community has a close relationship with psychological dimensions such as incompetence, powerlessness to voice, dependence and shame.